Women and poverty in Trinidad - Reddock, Rhoda (WAND St. MichaelBB, 1995)
Presents a well-supported claim that women are the major casualities in the assault by structural adjustment programmes. Seeks to get a deeper understanding of the gender mechanisms through which poverty, as a social process, is transferred from one generation to another.